SISTEM INFORMASI SIMPAN PINJAM PADA KOKAPURA (KOPERASI KARYAWAN) PT ANGKASA PURA I BANDARA UDARA AHMAD YANI SEMARANG (Information Technology and Telematics, 2013)
ABSTRACTKOKAPURA (Koperasi Karyawan) PT. Angkasa Pura I Bandara Udara Ahmad Yani Semarang. is a cooperative whose members are employees of PT. Angkasa Pura I and other employees in the scope of A Yani Semarang Airport. During this time, savings and loan transaction system in this case the loan is done directly / manually, that is a member fill out and submit the form directly to the savings and loan transaction  officer. With this application can help assist the officer in the process of inputting the data member, deposit data, loan data, and data installment, where the data will be used by the president for consideration for approval of the loan application. In addition, this application can help members to see the data stored, loan data, and the data installment The savings and loan applications by using the web- based programming languages PHP and MySQL. Savings and loan applications are available to provide ease of conveying information from the board to members of the savings and loan proes members, and accuracy in carrying out the savings and loan data processing in order to get optimal results. Keywords: Credit Unions, PHP, MySQL